Meningkatkan Keterampilan Komunikasi Dan Kerja Sama Tim Dalam Mengembangkan Potensi Siswa - Dian Asmara; Amelia Astrit Ananda; Indah Maulida Nurfaizah (CV. ITTC INDONESIA, 2026)
This community service activity aims to improve communication skills and teamwork in developing the potential of students at SMK Media Informatika. This program was conducted in response to students’ limited ability to communicate effectively and collaborate within teams, which are essential skills in both education and the workplace. The implementation methods included material presentations, interactive discussions, simulations, and group activities designed using a participatory approach. The results indicate an improvement in students’ understanding of effective communication, their ability to express ideas, and mutual respect within teamwork. In addition, students showed increased self-confidence and active participation during group activities. This community service program plays an important role in strengthening students’ soft skills to support personal development and better prepare them for future workplace challenges